2018
DOI: 10.29390/cjrt-2018-005
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea in patients with fibrotic diffuse parenchymal lung disease—characterization and treatment compliance assessment

Abstract: IntroductionRecent studies have reported a high prevalence of obstructive sleep apnoea (OSA) among patients with diffuse parenchymal lung disease (DPLD), mainly idiopathic pulmonary fibrosis (IPF). Effective OSA treatment appears to have a positive impact on morbidity and mortality in these patients. However, poor compliance to positive airway pressure (PAP) treatment in fibrotic DPLD patients has been reported. The aims of our study were to characterize patients with fibrotic DPLD and OSA and to assess their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…In addition to apoptosis, ER stress activation plays a critical role in the development of pulmonary fibrosis [34,35]. In the clinics, it was found that idiopathic pulmonary fibrosis is a characteristic of OSA patients [18]. It is well known that increased collagen deposition and synthesis are critical contributors of fibrosis [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to apoptosis, ER stress activation plays a critical role in the development of pulmonary fibrosis [34,35]. In the clinics, it was found that idiopathic pulmonary fibrosis is a characteristic of OSA patients [18]. It is well known that increased collagen deposition and synthesis are critical contributors of fibrosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, once ER stress is initiated, it is believed that fibrosis will be induced due to the acceleration of fibroblast proliferation and the expression of extracellular matrix protein, such as transforming growth factor-β1 (TGF-β1) and thrombospondin-1(TSP-1) [16,17]. In the clinics, pulmonary fibrosis was noted in OSA patients [4,18]. However, the major mechanisms underlying the effects of IH treatment on the pathological changes and dysfunction of pulmonary tissue are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence was not significantly different between patients with and without OSA. Besides, one study [20] reported that pulmonary hypertension was present in 18.2% OSA and 15.3% non-OSA patients, but in another study [13], no significant difference in the calculated systolic pulmonary artery pressure was found in subjects with and without OSA. https://doi.org/10.1371/journal.pone.0246878.g001…”
Section: Osa and Dpld Outcomesmentioning
confidence: 93%
“…Subgroup analyses were performed to evaluate sources of heterogeneity in the prevalence estimates between studies. The results revealed the prevalence to be higher as 76% (95% CI: 68-83%; I 2 = 69.2%) in the 13 studies enrolling IPF patients [10,[12][13][14][18][19][20][21][22][23][24][25][26] (Fig 2B), whereas in 4 studies including patients with connective tissue associated-ILD or sarcoidosis [20,21,25,26], the pooled prevalence of OSA was much lower (60%, 95% CI: 49-70%; I 2 = 0%), suggesting that the prevalence differed according to the type of DPLDs. Moreover, the prevalence of comorbid OSA in healthy controls and chronic obstructive pulmonary disease (COPD) were examined in two studies, and were found to be less frequent than in IPF (AHI 1.7 ± 1.0 vs 11.6 ± 7.2 [21]; prevalence 44% vs 62% [27]).…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 95%
See 1 more Smart Citation